2002
DOI: 10.1002/1521-4141(200206)32:6<1688::aid-immu1688>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

A reversible functional defect of CD8+ T lymphocytes involving loss of tetramer labeling

Abstract: We have observed that human CTL clones lose their specific cytolytic activity and cytokine production under certain stimulation conditions, while retaining an antigen‐dependent growth pattern.These inactive CTL simultaneously lose their labeling by an HLA‐peptide tetramer, even though the amount of TCR‐CD3 at their surface is not reduced. The tetramer‐negative cells recover tetramer staining and cytolytic activity after stimulation with tumor cells in the presence of a supernatant of activated lymphocytes. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…In contrast, the V␦1 ϩ T cells showed functional avidity to cells pulsed with the HIV-derived epitope peptide comparable to that of the other HIV-specific CD8 T cell subset (V␣12 ϩ ), which was competent for effector functions toward HIV-infected cells, indicating that the functional impairment observed in this study did not result from T cell anergy, skewed maturation of CD8 T cells in the periphery, or any defect in signal transduction machinery reported previously (1, 2, 6). There are a myriad of studies that focused on functional differences among Ag-specific (tetramer ϩ ) CD8 T cells for HIV (6, 7, 28 -30) as well as for other viruses and tumors (31)(32)(33), and such studies indicated functional heterogeneity of tetramer ϩ CD8 T cells. In our study we demonstrated that the duration of TCR-pMHC interactions could have considerable effects on the antiviral effector functions and proliferation capacity of HIV-specific CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the V␦1 ϩ T cells showed functional avidity to cells pulsed with the HIV-derived epitope peptide comparable to that of the other HIV-specific CD8 T cell subset (V␣12 ϩ ), which was competent for effector functions toward HIV-infected cells, indicating that the functional impairment observed in this study did not result from T cell anergy, skewed maturation of CD8 T cells in the periphery, or any defect in signal transduction machinery reported previously (1, 2, 6). There are a myriad of studies that focused on functional differences among Ag-specific (tetramer ϩ ) CD8 T cells for HIV (6, 7, 28 -30) as well as for other viruses and tumors (31)(32)(33), and such studies indicated functional heterogeneity of tetramer ϩ CD8 T cells. In our study we demonstrated that the duration of TCR-pMHC interactions could have considerable effects on the antiviral effector functions and proliferation capacity of HIV-specific CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was possible that assaying for other cytokines, such as TNF-␣ could have identified a higher percentage of Ag-specific cells, this would probably only have represented a minor contribution, as the percentage of Ag-specific cells identified by tetramer staining and IFN-␥ staining correlated well. One possible explanation for why roughly only half of OT1 control-vector cells stained positive may relate to their activation state, because it has been reported that even though Ag-specific T cells may retain both TCR and CD8 expression, they may not always stain tetramer positive or exhibit Ag-specific functional qualities (74,75). If the activation state is a relevant factor, this may also explain why roughly 25% of BL6 ovASBN-vector cells stained positive for high levels of exogenous dual ␣␤ TCR expression while only 10 -15% of BL6 ovASBN-vector cells were positive by IFN-␥ staining or tetramer analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies between cytokine release or cytolytic activity and tetramer binding have also been found in melanoma patients (38) and have been reported for cultured T cells (39). Furthermore, triggering T cell clones under certain in vitro stimulation conditions has been demonstrated to lead to a loss of tetramer labeling (40). Moreover, tetramer binding has been shown to be an active cellular process requiring cytoskeletal rearrangements (41), and efficient binding also depends on the integrity of lipid rafts on the surface of T cells (42).…”
Section: Discussionmentioning
confidence: 99%